ANALISIS NILAI TAMBAH PRODUK OLAHAN SUSU PADA USAHA RUMAH SUSU: PENDEKATAN METODE HAYAMI - Shinta Ayu Istiani; Soetriono Soetriono (JSEP (Journal of Social and Agricultural Economics), 2022)
Sales of dairy products tend to fluctuate during the covid-19 pandemic. This condition affects income. This study aims to (1) find out the dairy products, (2) find out the income of dairy products, (3) find out the added value of dairy products, (4) know the risk of income from dairy products. The research sample was selected using a purposive method. This research uses descriptive analysis, Hayami method added value analysis, and coefficient of variation. The results showed that (1) the products produced by the dairy house were pasteurized milk, fresh milk, and ice cream; (2) dairy products provide positive income; (3) the added value of dairy products provides positive added value to the dairy house because of the added value; (4) profitable dairy production activities. To increase the income of dairy houses during the pandemic, it is necessary to diversify other dairy products, such as making yogurt and milk crackers.